Surgical reconstructions for adult brachial plexus injuries. Part II: Treatments for total arm type - Li, Yen-Wei; Hsueh, Yu-Huan; Tu, Yung-Yi; Tu, Yuan-Kun (Injury, 2024)
Brachial plexus injuries (BPI) contribute not only to physical dysfunction but also to socioeconomic aspects and psychological disability. Patients with total arm-type BPI will lose not only the shoulder and elbow function but also the hand function, making reconstruction particularly challenging. Reconstructive procedures commonly include nerve repair, grafting, neurotization (nerve transfer), tendon transfer and free functional muscle transfer (FFMT). Although it is difficult to achieve prehensile hand function, most of patients with total arm-type BPI can be treated with satisfied outcomes. In addition to surgical techniques, comprehensive rehabilitation is another important factor for successful outcomes, and efficient communication can help to boost patient morale and eliminate uncertainty.